[PS 03-12] QUALITY OF CLINICAL PRACTICE GUIDELINES FOR HYPERTENSION: A SYSTEMATIC REVIEW USING THE AGREE II INSTRUMENT. (September 2016) - Zhang, Xiaowei; Zhao, Kun; Bai, Zhenggang; Yu, Jing; Bai, Feng
Abstract : Objective: To assess the quality of clinical practice guidelines (CPGs) for the prevention and treatment of hypertension. Design and method: To identify hypertension CPGs, a systematic search of the following relevant literature databases including PubMed, EMBASE, Web of Science, the National Guideline Clearinghouse (NGC), CNKI, Wan fang Data, VIP, and CBM was performed for the period from inception to July 2015 and used the AGREE II instrument to assess the quality of the included guidelines. Results: Eventually 41 guidelines met our inclusion criteria (10 CPGs in Chinese and 31 CPGs in English). The data of overall recommendation was presented as follow: strongly recommended (15%), recommended (29%), weakly recommended (51%), not recommended (5%). The scores of mean ± sd for all domains was: "Scope and Purpose" (58.65% ± 12.67%), "Stakeholder Involvement" (48.07% ± 11.41%), "Rigour of Development" (27.31% ± 12.29%), "Clarity of Presentation" (53.89% ± 11.09%, "Applicability" (40.10% ± 13.33%), "Editorial Independence" (38.75% ± 16.43%). All differences were statistically insignificant for all domains (P>0.05) according to publication time. CPGs using evidenced-based method had higher quality than non-evidence-based for all domains, the differences were statistically insignificant. All domain scores appeared slightly higher for CPGs developed by association and society versus those by individual. The difference results were statistically insignificant for all domains (P>0.05). Conclusions: Hypertension guidelines have flawed methodological quality. A more systematic approach in the development and reporting of these guidelines is recommended. The AGREE II instrument can be a useful tool to improve the quality of guidelines.